2003
DOI: 10.1093/occmed/kqg063
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for low back pain among office workers in Ibadan, Southwest Nigeria

Abstract: The occurrence of low back pain in this study is comparable with that reported in studies from more industrialized countries, but does not constitute a major cause of sickness absence in this group of workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
82
2
10

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(108 citation statements)
references
References 3 publications
14
82
2
10
Order By: Relevance
“…Being overweight or obese causes an increase in the pressure on the structures of the lower back and that may lead to lumbar disc herniation and subsequent LBP. These in agreement with studies reported an association between being overweight and experiencing LBP (14,15,16) . But in contrast to Chung et al 2005; Grimmer & Williams 2000 results (17,18) There was no association between regular physical activity and LBP in contrast with previous studies which reported the association between a lack of physical activity and LBP (19,20) .…”
Section: Discussionsupporting
confidence: 92%
“…Being overweight or obese causes an increase in the pressure on the structures of the lower back and that may lead to lumbar disc herniation and subsequent LBP. These in agreement with studies reported an association between being overweight and experiencing LBP (14,15,16) . But in contrast to Chung et al 2005; Grimmer & Williams 2000 results (17,18) There was no association between regular physical activity and LBP in contrast with previous studies which reported the association between a lack of physical activity and LBP (19,20) .…”
Section: Discussionsupporting
confidence: 92%
“…It is one of the most commonly treated disorders in out-patient physiotherapy clinics worldwide [19] and has been found to have significant impact on functional ability, thereby restricting occupational activities with marked socio-economic repercussion [20]. Studies have shown high prevalence rates of LBP in office workers [21], hospital staff [8], nurses [6], bricklayers [22], standing workers, agricultural workers and carpenters [23], commercial and private automobile drivers [24], among commercial drivers and motorcyclists [25]. However, little is known about the prevalence of low back pain among farmers in the rural areas, particularly in Nigeria.…”
Section: Resultsmentioning
confidence: 99%
“…These and other physical factors (such as posture and neck muscle endurance) have not been prospectively investigated specifically among office workers. Studies by Adedoyin et al 7 and Omokhodion and Sanya 8 reported high prevalence of Workrelated Musculoskeletal Disorders among office computer users in Nigeria but no reports on its association with working posture. .…”
Section: Introductionmentioning
confidence: 97%